2010
DOI: 10.14210/bjast.v14n2.p47-54
|View full text |Cite
|
Sign up to set email alerts
|

Fish communities of two tidal creeks in the Pinheiros bay, state of Paraná, southern Brazil

Abstract: Tidal creeks are meandering channels that are highly influenced by tidal changes and can experience substantial variation in salinity and depth over the course of the same day. The goal of the present work is to survey the ichthyofauna associated with these environments and to assess seasonal differences in their composition in tidal creeks of the euhaline sector of the estuary of the Paranaguá. Two tidal creeks of the Pinheiros bay were sampled monthly at the same time using fyke nets. A total of 13,755 fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…A. januaria (pelagic resident), A. brasiliensis (pelagic resident), C. edentulus (pelagic transient) and D. rhombeus (demersal transient)] observed in both bays are also typically abundant across other regional, shallow vegetated and non‐vegetated areas in the PEC (Vendel et al ., ; Félix et al ., ; Spach et al ., ; Contente et al ., ). For example, A. brasiliensis is among the most conspicuous species across regional tidal flats (Spach et al ., ; Contente et al ., ) and estuarine beaches (Félix et al ., ; Pichler et al ., ), while the other pelagic resident A. januaria has been noted in high abundance throughout creeks (Vendel et al ., ; Oliveira Neto et al ., ). Conversely, unlike in the present study, the transient D. rhombeus and C. edentulus have previously been recorded at comparatively lower relative abundances and dominance across tidal flats (Godefroid et al ., ; Oliveira Neto et al ., ; Falcão et al ., ; Contente et al ., ; Pichler et al ., ) or sporadically at estuarine beaches (Félix et al ., ; Pichler et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A. januaria (pelagic resident), A. brasiliensis (pelagic resident), C. edentulus (pelagic transient) and D. rhombeus (demersal transient)] observed in both bays are also typically abundant across other regional, shallow vegetated and non‐vegetated areas in the PEC (Vendel et al ., ; Félix et al ., ; Spach et al ., ; Contente et al ., ). For example, A. brasiliensis is among the most conspicuous species across regional tidal flats (Spach et al ., ; Contente et al ., ) and estuarine beaches (Félix et al ., ; Pichler et al ., ), while the other pelagic resident A. januaria has been noted in high abundance throughout creeks (Vendel et al ., ; Oliveira Neto et al ., ). Conversely, unlike in the present study, the transient D. rhombeus and C. edentulus have previously been recorded at comparatively lower relative abundances and dominance across tidal flats (Godefroid et al ., ; Oliveira Neto et al ., ; Falcão et al ., ; Contente et al ., ; Pichler et al ., ) or sporadically at estuarine beaches (Félix et al ., ; Pichler et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Other species are probably also influenced by broader patterns. For example, previous studies have shown that despite no evidence of reproduction, the pelagic transient C. edentulus is usually caught in multi‐specific aggregations of Engraulidae in waters adjacent to both bays during the wet and early‐dry seasons (Oliveira Neto et al ., ; Hackradt et al ., ). Considering the large abundance of juveniles observed here, the species may also use these areas for growth and predator avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, para que este seja suficientemente acurado, sugere-se a utilização de outros amostradores, como: rede capéchade nas margens para captura de Clupeiformes, Haemulidae e Carangidae (Ignácio & Spach, 2010); espinhéis de fundo e redes de deriva e fundeio nos canais para captura de elasmobrânquios e Ariidae, Sciaenidae e Carangidae de grande porte (Blaber, 1997); redes de espera de malhagem reduzida junto às macrófitas para captura de Characiformes e Pimelodidae (Vitule, 2007;Hilt et al, 2011); fyknets nas gambôas para captura de larvas e juvenis de Gerreidae, Centropomidae e Engraulidae (e.g. Oliveira-Neto et al, 2010); traineiras de pequeno porte no pelagial para captura de pequenos pelágicos, como Engraulidae, Carangidae, Clupeidae (e.g. Ecoutin et al 2009); trap-nets e ictiocidas para captura de táxons crípticos como Gobiidae, Bleniidae (Blaber, 1997).…”
Section: -Seleção Das Variáveis Explicativas E Respostas a Serem Mensunclassified
“…A taxa média anual de supressão/degradação de habitats ecologicamente vitais aos estuários tropicais, como manguezais e seagrasses, é c. seis vezes maior (3%.ano -1 ) do que a dos ecossistemas terrestres tropicais (c. 0.5%.ano -1 nas florestas tropicais; Achard et al, 2002;Duarte et al, 2008). Estima-se que 35% dos manguezais e 29% dos seagrasses já foram perdidos ou degradados no mundo (Valiela et al, 2001;MEA 2005;Orth et al, 2006;UNEP, 2006;FAO, 2007;Waycott et al, 2009), causando redução de 33% das pescarias costeiras viáveis, 69% das áreas 'berçário' e 63% dos serviços de filtragem e detoxificação desempenhados por filtradores, vegetação submersa e halófitas (Worm et al, 2006). A perda de biodiversidade e funções ecossistêmicas nos estuários também contribui à invasão biológica, ao declínio da qualidade das águas e à perda da proteção costeira contra eventos climáticos extremos (e.g.…”
Section: Introdução Geralunclassified